Analysis for step‐size optimisation on MPPT algorithm for photovoltaic systems. Issue 13 (1st October 2017) - Tang, Lei; Xu, Wei; Mu, Chaoxu
Abstract : As the output characteristic of photovoltaic arrays is a non‐linear function of external environment, the step‐size of maximum power point tracking (MPPT) algorithm should be regulated dynamically to improve the MPPT efficiency. However, the step‐size, essentially determining the performance of MPPT algorithm, is often designed for a particular system with certain working conditions. To solve this problem, an optimisation algorithm is proposed in this study, which can adjust the step‐size automatically. From the essence of optimisation problem, the tracking process can be converted into a maximum sequence which can be solved by several iteration algorithms. This study provides a simple and effective way to obtain the step‐size. Once the iteration method is selected, the performance of the MPPT algorithm has been decided. The analysis of convergence, convergence order and stability are presented in this study. Comprehensive simulation and experimental results demonstrate that this proposed algorithm has a good stable and dynamic characteristic.